Teachers’ Roles in Fostering Tolerance Values among Elementary School Students - Caesaria Primananda Wiedy; Maretha Dellarosa (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This study investigates teachers’ roles in fostering tolerance values among sixth-grade elementary school students at SDN Siwalankerto II/419 Surabaya. Using a qualitative case study approach, data were collected through classroom observations, semi-structured interviews, and document analysis involving classroom teachers, the deputy head of student affairs, the deputy head of curriculum, and students. The findings indicate that teachers foster tolerance through three interconnected roles: as role models, educators, and facilitators of habituation practices. Teachers demonstrated inclusive behavior through daily school routines, integrated tolerance into lesson planning and classroom interactions, and reinforced tolerant attitudes through sustained school culture practices. These findings align with Bandura’s Social Learning Theory, emphasizing that students develop social behavior through observation and imitation of meaningful models. The study highlights the importance of consistent teacher practices and inclusive school environments in developing tolerance values in elementary education